Reestruturação econômica e crise social no espaço metropolitano brasileiro - Baptista, Nelson Jakimczyk (2007)
This dissertation analyses the way in which economic reestrutucturation processs, that begins in the end of the decade of 70 and consolidade itself in the decade of 90, are impacting the main metropolis of the country, with the advance of labor fragility, unemployment and social inequality, that enlarge the vulnerability and degrade the life conditions of this inhabitants. In doing so, the work considers that the articulation of the brazilian economy to the process of globalization have contributed to a redefinition use of the metropolitan space, turning this areas into the core of social crises in contemporary Brazil.